Global library and information science - Abdullahi, Ismael (IFLA publications, 2017)
"This second edition of a well-known book presents international librarianship and library science through insightful and well written chapters contributed by experts and scholars from different regions of the world. All chapters will be revised and some new chapters will be included e.g. about Internet or Online Education. This book is a must-read by library science students and teachers, librarians, and anyone interested in Global Librarianship"